ANALISIS SEMIOTIKA ROLAND BARTHES TENTANG FENOMENA JILBOOBS - Hamidah Hamidah; Ahmad Syadzali (Faculty of Ushuluddin and Humanities, 2016)
Hijab/jilbab is a cloth to cover all of women’s body except face and two palms. Now, there is one controversial Hijab trend, which is Jilboobs phenomenon. Basically, jilboobs means have deviation meaning from the nature of veil. Jilboobs is a critic to Muslim women who wear hijab, but they still wear tight dress or blouse. It causes their indentation body looked very clear, especially in her chest. Then, the jilboobs phenomenon is a sign in fashion culture which very interference how Muslim teenagers to dress up now. The function of jibab is not to cover women genitals anymore, but it becomes a mode that break out the religion rules. The jilboobs phenomenon is a negative connotation from the real jilbab function. The writers used Semiotics theory from Roland Barthes to discuss this jilboobs phenomenon. It tried to reveal about abusing the real jilbab function as covering Muslim women’s genitals and a religion symbol.